Instilling National Awareness in Elementary School Students in Indonesia Through Cartoon Wayang - A, Astrid Sulistya; Y, Siti Hadiaty (Research Collaboration Community (RCC), 2024)
This paper discusses the significance of integrating traditional Indonesian culture, particularly wayang (puppet theatre), into modern educational practices to foster national awareness among elementary school students. By utilizing animated wayang cartoons, this initiative aims to connect young learners with their cultural heritage, instilling a sense of pride and identity that resonates with the values of Indonesian society. The paper outlines the methodology of implementation, discusses the results, and highlights the sustainability of such educational programs.